Facile construction of ultrathin SnOx nanosheets decorated MXene (Ti3C2) nanocomposite towards Li-ion batteries as high performance anode materials. (1st February 2019) - Sun, Xuan; Liu, Yang; Zhang, Jinyang; Hou, Linrui; Sun, Jinfeng; Yuan, Changzhou
Abstract: Recently, Ti3 C2 Tx MXene has drawn enormous attentions in Li-ion batteries (LIBs) due to its two dimensional (2D) open architecture, superior conductivity and low Li + diffusion barrier. However, further applications of Ti3 C2 Tx MXene are seriously limited by its moderate capacities. Herein, we fabricate SnOx @Ti3 C2 composites, where ultrathin SnOx nanosheets (NSs) of ∼5 nm in thickness are loaded uniformly on the interlayers and/or surfaces of Ti3 C2 matrix, through a facile hydrothermal method towards efficient lithium storage. Benefiting from ultrathin feature and large capacity of SnOx NSs, metallic conductivity of Ti3 C2 matrix, strong affinity between SnOx and Ti3 C2, the resulted SnOx @Ti3 C2 composites exhibit long-duration cycling stability and superior rate behaviors. Competitively, a large reversible capacity of ∼540 mAh g −1 still can be kept even after 1000 cycles at a current rate of 500 mA g −1 . Corresponding quantitative analysis reveals that capacitive and diffusion-controlled behaviors co-contribute to striking Li + storage properties of the hybrid anodes, wherein the former dominates. This work demonstrates that the MXene-based materials hold a significant promising for advanced next-generation LIBs. Graphical abstract: 2D nanohybrid of ultrathin SnOx nanosheets in situ loaded uniformly in the interlayers and/or on the surfaces of Ti3 C2 matrix was smartly synthesized, and exhibited superior lithium storage as a competitive anode for Li-ion batteries. Image 1 Highlights: The SnOx @Ti3 C2 nanohybrids are fabricated through simple hydrothermal strategy. Ultrathin SnOx nanosheets are uniformly in interlayers and/or on surfaces of Ti3 C2 . The SnOx @Ti3 C2 exhibits superior rate behaviors with synergetic contributions from the two. Pseudocapacitive contribution dominates Li-storage behaviors of the nanohybrid.